PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Hafidz, Muhammad Fajar; Ghozali, Imam (Diponegoro Journal of Accounting, 2024)
The aim from this study is investigate the relationship between good corporate governance on intellectual capital disclosure. The independent variables used in this research is board size, the proportion of independence, board tenure, blockholder ownership, board meeting frequency, audit committee size, and audit committee meeting frequency. Then the dependent variable in this research is intellectual capital disclosure. The population used in this study consists of companies in manufacturing sector listed on the Indonesian Stock Exchange. Using purposive sampling method, the 114 samples used from companies in manufacturing sector which published annual reports for the period 2019-2021. Multiple regression analysis is used in this study for testing the relationship between board size, the proportion of independence, board tenure, blockholder ownership, board meeting frequency, audit committee size, and audit committee meeting frequency on intellectual capital disclosure. The results from this study show that board meeting frequency and audit committee size that has positive and significant impact to intellectual capital disclosure.